2021
DOI: 10.1007/s13730-021-00630-w
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy complicated by immune thrombocytopenia treated with low-density lipoprotein apheresis: a case report and literature review

Abstract: Immune thrombocytopenia (ITP) may lead to membranous nephropathy (MN). Here, we report a case of MN complicated by ITP and validate the hypothesis that circulating antiplatelet antibodies cause MN using immunofluorescence analysis for immunoglobulin (Ig) G subclass and anti-phospholipase A2 receptor (PLA2R) antibodies. A 39-year-old Japanese man with ITP, who had been treated with prednisolone for 10 months, achieved a stable disease condition. However, 4 months after tapering the dose down to 10 mg prednisolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The overall 10-year survival rate is about 80%, but the prognosis depends largely on which manifestations predominate. 12 , 13 The aim of this study is to identify the frequency and patterns of mixed connective tissue disease to characterize his epidemiology in Sudanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…The overall 10-year survival rate is about 80%, but the prognosis depends largely on which manifestations predominate. 12 , 13 The aim of this study is to identify the frequency and patterns of mixed connective tissue disease to characterize his epidemiology in Sudanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, no clinical signs of nephropathy were found in aPLs carriers with thrombocytopenia. Lande et al [17] and Nishizawa et al [18] reported cases of membranous nephropathy complicated by ITP, but the aPLs profile was not further elucidated. The proportion of each separate kind of aPLs was similar between the two groups, except that LA was more frequent in thrombocytopenic APS patients but lacked statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases have previously reported a link between MN as well as ITP and were treated using prednisolone [ 19 ], a combination of prednisolone with immunosuppressive therapy [ 15 , 16 ], rituximab [ 20 ], or low-density lipoprotein apheresis [ 21 ]. However, there are no reports on patients with coexisting MN and ITP whose condition improved after gastric Helicobacter pylori infection eradication.…”
Section: Discussionmentioning
confidence: 99%